New affiliation-hiding authenticated key exchange protocol - Ya-min WEN; Zheng GONG (Tongxin xuebao)
A new affiliation-hiding authenticated key agreement protocol was proposed.The proposal enables two anonymous users to accomplish a successful secret authentication and key agreement when their groups set intersection is non-empty and the cardinality of the set intersection should not be less than a threshold value.Meanwhile,the affiliations of groups outside of the set intersection remain confidential.The proposal is provably secure under the random oracle model,and the performance of the scheme is still competitive.